Answer:
[tex] 6x + 4 = 12x - 20 [/tex]
[tex] x = 4 [/tex]
Step-by-step explanation:
Let "x" be the number.
Product of 6 and x (6*x), increased by 4 = [tex] 6x + 4 [/tex]
Product of 12 and x, (12*x), decreased by 20 = [tex] 12x - 20 [/tex].
Set both expressions equal to each other and solve for x as shown below:
[tex] 6x + 4 = 12x - 20 [/tex] (equation)
Subtract 12 from both sides
[tex] 6x + 4 - 12x = 12x - 20 - 12x [/tex]
[tex] -6x + 4 = -20 [/tex]
Subtract 4 from both sides
[tex] -6x + 4 - 4 = -20 - 4 [/tex]
[tex] -6x = -24 [/tex]
Divide both sides by -6
[tex] \frac{-6x}{-6} = \frac{-24}{-6} [/tex]
[tex] x = 4 [/tex]